Internal dosimetry for alpha emitters radiopharmaceuticals in biological tissue studied with the FLUKA code - Valente, Mauro Andrés (2014)
Trabajo presentado en el X Latin American Symposium on Nuclear Physics and Applications (X LASNPA), 1-6 diciembre 2013. Montevideo, Uruguay.